Proses Kegiatan Digital Marketing Communication Dalam Membuat Konten Wisata & Otomotif di VF Digital Indonesia - Siti Choeriyah Tauhid (Swadaya: Indonesian Journal of Community Empowerment, 2021)
Field Work Practice (PKL) is an alternative in implementing the national curriculum as a coursethat aims to produce graduates who are professional in their fields. With the development oftechnology and science, we are required to compete in the world of work by improving the qualityof human resources who have good quality knowledge, good personality components and skillsthatcan be used in the life of society and the state in the field of work they do. Therefore, humanresources are currently an obligation for managers of both public and private organizations bothleaders and members of the organization are required to know how humans as sources of power orenergy have the ability to be used in building organizations and students have the opportunity todevelop ways of thinking, provide useful ideas and can increase their knowledge. Digitalmarketing is an effort to promote a brand or brand and market it using digital media, such as theinternet. Currently, digital marketing is very popular used by most marketers around the world.This is the impact of the increasing world of the internet and technology that makes the internet avery prospective market.Keywords: Digital Marketing Communication, Digital Tourism, Automotive content, TourismContent.